Since the problem does not provide information regarding values of x and y, you can consider that x and y do not have common factors, hence, the given difference x - y cannot be furthermore factored.
If the problem provides the information that x is a divisor of y, hence, you may write y such that:
`y = k*x` , where k is constant
Replacing kx for y yields:
`x - y = x - kx`
You may factor out x, such that:
`x - kx = x(k - 1)`
If the problem provides the information that y is a divisor of x, hence, you may write x such that:
`x = k*y`
Replacing ky for x yields:
`x - y = ky - y`
You may factor out y, such that:
`ky - y = y(k - 1)`
Hence, the original given difference, cannot be factored, unless the problem specifies a relation between x and y.
you cant factorize it
x-y = (√x)2 - (√y)2= (√x + √y) (√x - √y)
Similary (x-y) = (√x)n - (√y)n can be factorized.
Any Comment Plz.
like what wonderwhitey said (x-y) can't be further factored. If you meant (x^2 - y^2) the answer is (x+y)(x-y).
this is a factor already i'm afraid.